- - رضا تهرانى; سیدجلال صادقى شریف (تحقیقات مالی, 2004)
This study tends to present the result of the conditional CAPM (CCAPM) study in Tehran Stock Exchange Market. It tends to use CCAPM to lead portfolio managers and other investors to optimize their investments regarding conditional risk and return relation in Tehran Stock Exchange Market. The study results shows that conditional CAPM is able to describe the cross-section relation & risk- returns behavior in upward & downward markets in Tehran Exchange. It says that the relation between risk & return is subject to market movements, as: in the upward markets when risk goes up, the expected return goes up too. But in the downward markets when the risk goes up, expected return comes down. So in the downward markets when market premium is negative, the expected return decreases while the risk increases. This study is important because Tehran Exchange market is young & growing. It says that we can use improved models in this young market the same as markets in western countries.